Creativity Of English Tutorial Activities In Helping Students Understanding Online Learning In Elementary School - Farah Zafiroh Nuradi; Elisa Kurniawati; Nur Faizah; Umi Rachmawati (Prosiding University Research Colloquium, 2021)
Because the covid-19, learning that was originally at school has now become home throughthe online system. Online learning has various limitations, for example, the absence ofgadget facilities (cell phones and laptops), low understanding of digital media and limitedsignal. Students who usually study in class and are explained directly to the teacher, nowthe teacher only gives reading explanations and gives assignments, this makes studentsmore confused because there is no clear explanation but are forced to understand by doingassignments. This study uses descriptive qualitative research that describes tutoringservices in reducing difficulties in student learning during the COVID-19 period. Studentsalways ask to be helped with assignments. Students need assistance in learning, so thatthe material can be easily understood optimally.